PENGARUH PERLAKUAN JENIS PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN IKAN PELANGI Marosatherina ladigesi [Effect of Feeds Type on Growth of Rainbowfish, Marosatherina ladigesi] - Triyanto Triyanto; Djamhuriyah S. Said (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2006)
The research about effect of feeds type on fish have common done. However information about appropriate feeds type for the growth of Marosatherina ladigesi has been unknown well. The research was conducted in Laboratory of Research Center for Limnology-LIPI in June - August 2006. The research aimed to determine the effect of feed to growth and survival rate of M. ladigesi. This Research conducted by utilizing four different feeds type, namely Daphnia, Chironomus, Tubificidae, and pellet. The result showed that different kind of feeds type have an effect on growth and survival rate of M. ladigesi. Feed from Tubificidae showed highest growth of total length 1.19 cm (0,020 cm/day). While feed type from Chironomus showed highest growth of weight 0.47 g (0.008 g/day) and highest survival rate 100%.